Role of Primary Health Care in child hospitalization due to pneumonia: a case-control study - Juliana Coelho Pina; Suzana Alves de Moraes; Isabel Cristina Martins de Freitas; Débora Falleiros de Mello
Objective: to evaluate the association of primary health care and other potential factors in relation to hospitalization due to pneumonia, among children aged under five years. Method: epidemiological study with a case-control, hospital-based design, which included 345 cases and 345 controls, matched according to gender, age and hospital. Data were collected using a pre-coded questionnaire and the Primary Care Assessment Tool, analyzed by means of multivariate logistic regression, following the assumptions of a hierarchical approach. Results: the protective factors were: family income >US$216.12 (OR=0.68), weight gain during pregnancy ≥10 kg (OR=0.68), quality of Primary Health Care (OR for scores >3.41=0.57; OR for scores >3.17 and ≤3.41=0.50), gastro-esophageal reflux (OR=0.55), overweight (OR=0.37) and birth interval ≥48 months (OR=0.28). The risk factors included: parity (2 childbirths: OR=4.60; ≥3 childbirths: OR=3.25), out-of-date vaccination (OR=2.81), undernutrition (OR=2.53), history of wheezing (≥3 episodes OR=2.37; 1 episode: OR=2.13), attendance at daycare center (OR=1.67), and use of medicines over the past month (OR=1.67). Conclusion: primary health care and its child health care practices, such as nutritional monitoring, immunization, care to prevalent illnesses, prenatal care and family planning need to be prioritized to avoid child hospitalization due to pneumonia.